A daily within-person investigation on the link between social expectancies to be busy and emotional wellbeing: the moderating role of emotional complexity acceptance. Issue 4 (19th May 2022) - Lua, Verity Y. Q.; Majeed, Nadyanna M.; Leung, Angela K.-y.; Hartanto, Andree
ABSTRACT: With postmodern societies placing a strong emphasis on making full use of one's time, it is increasingly common to extol busy individuals as more achieving. In this context, although feeling a social expectation to be busy might imply that individuals are regarded as competent and desirable, its accompanying stressors may also detrimentally impact their mental health. Utilising data from a seven-day diary study, the current research examined the relationship between people's daily perceived pressure to be busy and their daily emotional wellbeing. Multilevel modelling revealed that daily social pressure to be busy was a significant predictor of daily negative affect, anxiety, and depressive symptoms at the within-person level. Of import, individuals' trait emotional complexity acceptance moderated these relationships, with those lower on emotional complexity acceptance reporting significantly higher negative affect, anxiety, and depressive symptoms on days they felt greater social pressure to be busy. These effects were not observed among those higher on emotional complexity acceptance. Together, the current findings suggest that social pressure to feel busy is generally related to poorer daily emotional wellbeing, and that those with higher trait emotional complexity acceptance have an advantage of maintaining their emotional wellbeing in the face of such a social pressure.